2013
DOI: 10.1371/journal.pone.0076275
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Tuberculosis Treatment in Patients with Diabetes Mellitus Treated in the Revised National Tuberculosis Control Programme in Malappuram District, Kerala, India

Abstract: SettingsKerala State, India has reported the greatest dual burden of Tuberculosis (TB) and Diabetes Mellitus (DM). Malappuram district in Kerala has monitored and recorded DM status and its control from 2010 under Revised National Tuberculosis Control Program (RNTCP).ObjectivesTo assess, under programme conditions, comprehensiveness of recording DM status among TB cases and the TB treatment outcomes among DM patients (disaggregated by glycemic control) and compare with-non DM patients.DesignThis retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
3
35
3
Order By: Relevance
“…The overall prevalence of HIV (20.0%) is higher than the DM prevalence (8.3%) observed in the study. The finding is in accordance with the study done in Gondar-Ethiopia [ 18 ] but in contrast to the study result reported from Malappuram-India [ 39 ]. This might be due to the high prevalence of HIV in the study area.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall prevalence of HIV (20.0%) is higher than the DM prevalence (8.3%) observed in the study. The finding is in accordance with the study done in Gondar-Ethiopia [ 18 ] but in contrast to the study result reported from Malappuram-India [ 39 ]. This might be due to the high prevalence of HIV in the study area.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to studies done in Malappuram-India [ 39 ], Tamil Nadu–India and Trivandrum–Kerela India [ 29 , 32 ], the prevalence of PTB among patients in the TBDM group was higher than TBNDM group. This might be related to defects in immune functions and decrease capacity of alveolar macrophage to eliminate mycobacterial infection in DM patients [ 3 – 4 , 9 , 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, half of all retreatment patients had prediabetes or diabetes, which was not the case for patients admitted with an initial episode of TB or MDR-TB. The diabetes co-prevalence among our population contrasts with the far higher proportions found by HgbA1c screening in studies from Southeast Asia, where the community burden of diabetes is greater [8,17], but demonstrates the importance of performing such local investigation before adopting a widespread policy.…”
Section: Discussioncontrasting
confidence: 75%
“…However, human studies have not been able to confirm this finding. Two retrospective studies failed to find a negative association between the status of DM control during treatment and treatment response 23 31. However, a prospective study from Peru reported that the hazard rate of culture conversion among those with documented DM control was 2.2 (95% CI 1.1 to 4.1) compared with unrecognised or uncontrolled-DM.…”
Section: Discussionmentioning
confidence: 99%